Stochastic modeling of hourly rainfall processes [compact disc] - Fadhilah Yusof 560555; Zalina Mohd. Daud, supervisor (2008)
Thesis (Doktor Falsafah (Fakulti Sains)) - Universiti Teknologi Malaysia, 2007